2017
DOI: 10.1016/j.nutres.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and opportunities for nutrition research in relation to non-communicable diseases in Arab countries: Call for an informed research agenda

Abstract: Effective public health nutrition interventions are needed to curb the escalating prevalence of non-communicable diseases (NCDs) in many Arab countries. In order to generate the scientific evidence needed for the success of these interventions, an informed research agenda should be developed. The purpose of this review is to identify gaps and opportunities for research on nutrition and NCDs among Arab countries, which is an important step towards the formulation of this research agenda. Published papers that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Few studies focus on infants and children ≤2 years of age in the EMR, 18 and none exist in Lebanon, rather studies of the determinants of nutritional status are among older children (>2 years), 19 adolescents, 13 and adults. 20 Further, the studies do not account for the hierarchical nature among the multilevel determinants of nutritional status, nor stratify the analysis by child's sex.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Few studies focus on infants and children ≤2 years of age in the EMR, 18 and none exist in Lebanon, rather studies of the determinants of nutritional status are among older children (>2 years), 19 adolescents, 13 and adults. 20 Further, the studies do not account for the hierarchical nature among the multilevel determinants of nutritional status, nor stratify the analysis by child's sex.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A study in Egypt showed that micronutrient deficiency states co-exist with obesity and that serum Zinc and iron correlated with HDL and negatively with leptin and cholesterol (28) . Other studies have shown significant gaps in the diet of populations living in the EMR (29,30) . Vitamin D intake was found to improve cases with heart failure (31) and have been shown to have cardiopotent metabolic effects on HBP (32) .…”
Section: Discussionmentioning
confidence: 94%
“…However, recent national epidemiological studies in Lebanon regarding the nutrition transition, adolescents' obesity and NCDs' prevalence are lacking; thereby, researchers rely solely on targeted research based on specific samples (Nasreddine et al, 2012). A systematic review by Naja et al (2017) exploring the studies on dietary patterns in Lebanon, indicated that very few studies included data collected from children and adolescents with most studies focusing on the examination of nutrition in isolation excluding other environmental factors (Naja et al, 2017).…”
Section: Background Informationmentioning
confidence: 99%